Pengaruh WFH (Work From Home), Desain Pekerjaan, dan Beban Kerja Terhadap Stres Kerja Pada Masa Pandemi Covid-19 (Studi Pada Guru SMA Negeri 6 Malang) - Muhammad Arief Zan Razak; Pardiman Pardiman; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This study aims to determine the effect of WFH (Work From Home), Job Design, and Workload on Work Stress in Teachers of SMA Negeri 6 Malang. The The sample used in this study consisted of 62 teachers. The data analysis method used in this study is quantitative data analysis using multiple linear regression analysis. The tests for the data used are the simultaneous hypothesis test (f) and the partial hypothesis test (t). The results also showed that the independent variable had a significant effect on the dependent variable. Based on partial test results WFH (Work From Home) variable has a positive and significant effect on work stress, job design has a negative and insignificant effect on work stress, workload has a positive and significant effect on work stress. Keywords: WFH (Work From Home), Job Design, Workload, and Work Stress